Adsorption of heavy metal ions from aqueous solution by carboxylated cellulose nanocrystals - Yu, Xiaolin; Tong, Shengrui; Ge, Maofa; Wu, Lingyan; Zuo, Junchao; Cao, Changyan; Song, Weiguo (Journal of environmental sciences (China), 2013)
A novel nanoadsorbent for the removal of heavy metal ions is reported.Cotton was first hydrolyzed to obtain cellulose nanocrystals（CNCs）.CNCs were then chemically modified with succinic anhydride to obtain SCNCs.The sodic nanoadsorbent（NaSCNCs） was further prepared by treatment of SCNCs with saturated NaHCO 3 aqueous solution.Batch experiments were carried out with SCNCs and NaSCNCs for the removal of Pb 2＋ and Cd 2＋.The effects of contact time,pH,initial adsorption concentration,coexisting ions and the regeneration performance were investigated.Kinetic studies showed that the adsorption equilibrium time of Pb 2＋ and Cd 2＋ was reached within 150 min on SCNCs and 5 min on NaSCNCs.The adsorption capacities of Pb 2＋ and Cd 2＋ on SCNCs and NaSCNCs increased with increasing pH.The adsorption isotherm was well fitted by the Langmuir model.The maximum adsorption capacities of SCNCs and NaSCNCs for Pb 2＋ and Cd 2＋ were 367.6 mg/g,259.7 mg/g and 465.1 mg/g,344.8 mg/g,respectively.SCNCs and NaSCNCs showed high selectivity and interference resistance from coexisting ions for the adsorption of Pb 2＋.NaSCNCs could be efficiently regenerated with a mild saturated NaCl solution with no loss of capacity after two recycles.The adsorption mechanisms of SCNCs and NaSCNCs were discussed.